Transformation of Sudan's agrifood system structure and drivers - Diao, Xinshen; Pauw, Karl; Raouf, Mariam; Siddig, Khalid; Thurlow, James; Ellis, Mia (International Food Policy Research Institute, 2023)
Since the secession of South Sudan in 2011, the Sudanese economy has faced an unprecedented economic downturn caused by the loss of around 75 percent of oil revenue, civil strife, and political instability (Alhelo, Siddig, and Kirui 2023), and more recently, by the impacts of the global COVID-19 pandemic and the Russia-Ukraine war (Abay et al. 2023). The political conflict between the civilians and military entities after the fall of the Inghaz regime and the ongoing conflict between the Sudanese Armed Forces (SAF) and the Rapid Support Forces (RSF) are driving further deterioration of the economy (Abushama et al. 2023).